Elemental partitioning, lattice misfit and creep behaviour of Cr containing γ′ strengthened Co base superalloys - Povstugar, I.; Zenk, Carolin; Li, R.; Choi, P. -P.; Neumeier, Steffen; Dolotko, O.; Hoelzel, M.; Göken, Mathias; Raabe, D. (Materials Science and Technology, 2016)
Novel Cr containing Co-Al-W base superalloys were studied by atom probe tomography and neutron diffraction. Cr is found to predominantly partition to the γ matrix and decrease partitioning of W to γ′. Furthermore, Cr significantly enhances the γ′ volume fraction, decreases the γ/γ′ lattice misfit and deteriorates the creep resistance. Addition of Ni to the Cr containing alloys affects partitioning of W and Al, further decreases the lattice misfit and results in the formation of irregularly shaped precipitates. Al, W and Cr tend to occupy the ‘B' sublattice in the γ′-A3B phase (L12 type), while Co and Ni reside in the ‘A' sublattice.<br
WW1::1068
Keywords: Cobalt base superalloys; Creep; Atom probe tomography; Partitioning; Lattice misfit; Neutron diffraction